2021
DOI: 10.1186/s12870-021-03065-8
|View full text |Cite
|
Sign up to set email alerts
|

TeaAS: a comprehensive database for alternative splicing in tea plants (Camellia sinensis)

Abstract: Alternative splicing (AS) increases the diversity of transcripts and proteins through the selection of different splice sites and plays an important role in the growth, development and stress tolerance of plants. With the release of the reference genome of the tea plant (Camellia sinensis) and the development of transcriptome sequencing, researchers have reported the existence of AS in tea plants. However, there is a lack of a platform, centered on different RNA-seq datasets, that provides comprehensive inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Among these samples, retained intron (RI) were the predominant AS type. This observation is in accordance with that of previous reports on maize [41], cotton [42], and tea plant [43]. We next comprehensively identified the differentially expressed AS genes (DAGs) under different shading rates of solar-withering.…”
Section: Rna Demethylation Modulates As Events By Influencing the M 6...supporting
confidence: 90%
“…Among these samples, retained intron (RI) were the predominant AS type. This observation is in accordance with that of previous reports on maize [41], cotton [42], and tea plant [43]. We next comprehensively identified the differentially expressed AS genes (DAGs) under different shading rates of solar-withering.…”
Section: Rna Demethylation Modulates As Events By Influencing the M 6...supporting
confidence: 90%
“…In order to construct a relatively complete database, we collected the genome assembly and Pacbio data of 6 tea plant varieties, including “Shuchazao” [ 14 ], “Longjing43” [ 14 ], “Tieguanyin” [ 16 ], “Biyun” [ 15 ], “Huangdan” [ 17 ], “DASZ” [ 18 ] and “Yunkang 10” [ 1 ]; 238 whole-genome resequencing datasets (Additional file 1: Table S 1 ) [ 4 , 13 , 16 ]; a F1 hybrid population with 96 offspring [ 2 ]; 213 transcriptome sequencing data (Additional file 2: Table S 2 ) [ 18 ]. The above data were used for the identification of SNPs, Indels, SSRs and SVs; an additional 66 transcriptomes were collected from NCBI ( https://www.ncbi.nlm.nih.gov/ ) for expression abundance calculations (Additional file 3: Table S 3 ) [ 22 ].…”
Section: Construction and Contentmentioning
confidence: 99%
“…For tea trees, some databases have been successfully constructed in previous studies. For example, Xia et al constructed the first tea tree genome database [ 20 ]; Zhang et al collected 261 high-quality RNA-Seq experiments to construct a tea plant gene co-expression database [ 21 ]; Mi et al collected 66 different tea tree transcriptome datasets to construct a rich alternative splicing database [ 22 ]; and Singh et al constructed the first-generation tea plant haplotype map website [ 23 ]. However, compared with other crops [ 24 , 25 ], the genome-wide variation database of tea plant population remains unreported.…”
Section: Introductionmentioning
confidence: 99%
“…The whole-length CsTPS1 contains a 1758-bp open reading frame (Figure S1) that encoded 585 amino acids (Figure S2); there were 83 fewer amino acids in the AS form (referred to as CsTPS1-AS ) (Figure 2A and Figure S2). The AS form of CsTPS1 was confirmed based on an AS database for tea plants (TeaAS,http://www.teaas.cn/index.php) (Mi et al, 2021). The expression of CsTPS1 and its AS isoform (CsTPS1 -AS ) was quantified in response to pathogen infection.…”
Section: Expression Levels Of Eight Candidate Csges Genes In Pathogen...mentioning
confidence: 99%
“…Alternative splicing (AS) can generate different mRNA splicing isoforms from a single mRNA precursor via different splicing sites (Li et al, 2020), and this can result in diverse protein isoforms (Laloum et al, 2018). An increasing number of studies have shown that AS plays an important role in the growth, development, and abiotic and biotic stress tolerance of plants (Mi et al, 2021;Posé et al, 2013). AS is also key in the biosynthesis of secondary metabolites (Zhao et al, 2014) and the response to pathogen infection (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%